Serratia marcescens in the neonatal intensive care unit: A cluster investigation using molecular methods. Issue 7 (July 2020) - Yeo, Kee T.; Octavia, Sophie; Lim, Kian; Lin, Cui; Lin, Raymond; Thoon, Koh C.; Tee, Nancy W.S.; Yung, Chee F.
Abstract: Background: Serratia marcescens (S. marcescens) is associated with nosocomial infections with significant morbidity and mortality in the neonatal intensive care units (NICU). We describe the control of a multi-clonal S. marcescens infections outbreak in our tertiary-level NICU and the application of molecular typing using repetitive element palindromic PCR ( rep-PCR) and next generation sequencing (NGS) in the investigation. Methods: Outbreak investigation was performed where clinical, spatial and epidemiologic links were established. Screening of all infants in the NICU and the environment was performed. Rep-PCR and NGS methods were used to identify potential environmental sources of infections and clustering among cases. Results: Eleven cases were detected during the outbreak period: mean gestational age 27 weeks (range: 24–32), predominantly male (82%), mean age of infection 24 days (range: 6–51). Six infants were treated for conjunctivitis and one for bacteraemia. Identification of colonized infant via a point prevalence survey and cohorting of all infected/colonized patients were implemented. We performed environmental swabbing of surfaces, water outlets, chlorhexidine hand wash solutions and hand hygiene hand rubs. Both rep-PCR and NGS classified the 11 case isolates into 5 types. No point source was identified except for a single positive environmental isolate from a sink which was clonally distinct from the cases. Conclusion: Identification and cohorting of infected/colonized patient was important in the control of S. marcescens outbreak in the NICU. The utility of rep-PCR was comparable to NGS in providing molecular information to develop S. marcescens outbreak control strategies.